Waqf for Education: Islamic Philanthropic Initiative in Pakistan and Bangladesh - Mansur, Muhammad; Rama Bagus Sanjaya, Try; Razali, Razali; Pratama, Vio (MD Research Center Yogyakarta, 2025)
This study investigates the potential of waqf (Islamic endowment) as an alternative funding mechanism for higher education in Pakistan and Bangladesh. Employing a qualitative literature review method, the research analyzes the distinct management models and challenges inherent in both countries. In Pakistan, waqf assets for education are primarily managed by private entities with minimal state coordination, whereas Bangladesh faces systemic issues of regulatory weakness and low public engagement despite its rich historical tradition of waqf. The findings indicate that this potential can be optimized through innovative instruments like cash waqf, which offers flexible funding for scholarships, infrastructure, and institutional operations. The study concludes that strategic measures—including regulatory strengthening, enhanced transparency in governance, and public awareness campaigns—are essential to maximize waqf's contribution. Effective implementation could reduce reliance on public and external funding, positioning waqf as a sustainable pillar for educational development in both nations.